Analysis of Human Factors that Influence Contractors' Risk Management Attitudes in Sumatra Island in Construction Projects - Lisherly Reginancy Debataraja (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
Project risk assessment serves as an effective tool for overseeing cost, and time, and achieving technical performance in construction projects. The construction industry frequently contends with various uncertainties, which can lead to potential risks such as delays, cost overruns, and compromised quality in building and road construction ventures. Consequently, adept project risk management becomes crucial in the decision-making process of construction companies, ultimately determining project success or failure. This paper aims to assess the prioritize the specific factors influencing contractors' risk attitudes in these companies. The study employed simple random sampling under probability techniques. Data collection involved a thorough review of pertinent literature and the use of a questionnaire employing a five-point Likert scale ranging from (1) very low/very disagree to (5) very high/very agree. The sample size used for analysis was 47 companies, with a particular focus on the Sumatra construction companies. This study was analyzed using Statistical Package for Social Science (SPSS) version 23.0 for Microsoft Windows and a reliability test with Cronbach's alpha. The finding of this study is primary factors influencing contractors' risk attitudes are as follows: educational background, physical health, emotional intelligence, work experience, and professional competence, The results of this research can provide decision-makers with valuable insights into strategies for effectively managing contractors' risk attitudes, thus furnishing stakeholders with the requisite knowledge to enhance risk management performance within the Sumatera construction companies.